Problem Based Learning Curriculum Management in Improving Learning Motivation - Fahmi, Muhammad (JURNAL IJ-ATL, 2022)
In the face of declining student motivation in language learning, particularly in Arabic instruction at the secondary education level, innovative curriculum models are urgently required. This study explores the implementation of Problem-Based Learning (PBL) curriculum management as a strategic response to enhance student motivation in Arabic language learning. The research aims to analyze how curriculum planning, organizing, implementation, and evaluation based on PBL principles contribute to learner engagement and active participation. Employing a qualitative descriptive approach, data were obtained through interviews, observations, and documentation at MA Ma’arif NU 1 Kemranjen. The results show that PBL-based curriculum management effectively boosts learning motivation by presenting real-life contextual problems, fostering collaborative learning environments, and applying continuous assessment that encourages student autonomy. These findings affirm that PBL not only enriches the learning process but also supports the development of critical thinking and problem-solving abilities necessary for mastering Arabic. It is concluded that structured implementation of PBL in curriculum management is a promising path to revitalize motivation and learning outcomes in Arabic education.